Sedekah Materi dan Non-Materi dalam Islam: Studi Kritik Hadis - Annisa Safira; Carsam; Deni Miharja (Gunung Djati Conference Series, 2022)
This study aims to discuss the hadith about alms. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about alms in Muslim history No. 4689. The results and discussion of this study indicate that the status of the hadith regarding alms has an authentic quality that meets the qualifications of maqbul ma'mun bih for the practice of Islam from the aspect of wisdom, fiqh review, and alms etiquette. This study concludes that the hadith narrated by Muslim No. 4689 regarding alms in the form of material and non-material such as relevant services used for understanding the values of alms and character building and their implementation in social life in Indonesia.